Pluck And Pack Rambutan 2015 - Abang, Mohamad (UiTM Sarawak, 2016)
Unit Pengurusan Ladang organized a Pluck And Pack Rambutan 2015 event from 28th to 30th December 2015. This event was opened to the staff and members of the public from Samarahan and Kuching, to experience rambutan fruit picking. This was the 4th time this activity has been organized since it started in 2010. Around 350 participants took part in this event. Adults were charged an admission fee of RM1 each while children below six years old could enter free of charge. Participants could bring home as many rambutans as they wanted with a charge of RM1.00 per kg for staff and RM2.00 per kg for the public.